A Case of Severe Asymptomatic Aortic Coarctation in an Adult Female. (23rd August 2011) - Tsikrikas, Spyros; Charalampous, Charalampos; Letsas, Konstantinos P.
Abstract : Coarctation of the aorta is typically a disease of childhood and early adulthood, and there is a reduced life expectancy in patients who have not undergone correction. Survival to older age is rare, due to severe cardiovascular complications. We describe the case of a woman first diagnosed with coarctation of aorta at an advanced age.